Histopathological Evaluation of Rabbit Hepatic Tissue Due to Remote Ischemic Reperfusion of Acute Limbs Injury Conducted with Ischemic Precondition and Hypothermic - Marolop Pardede (JURNAL WIDYA MEDIKA, 2020)
Acute limb ischemia (ALI) is an emergency that occurs due to a rapid decrease in perfusion to limbs which can result in mitochondrial dysfunction, causing disturbances in distant organs such as liver. There are various ways to reduce the effects including treatment of hypothermia and ischemic preconditions. So, this study was made to see any differences in liver tissue damage as a result of reperfusion distant ischemic injury between the untreated and treated groups of hypothermia and ischemic precondition in cases of acute limb ischemia. This study is a true-experimental, with the New Zealand White (NZW) male rabbits as the samples and it divided into three groups, untreated rabbit group (as a control), treated with ischemic preconditioning group and hypothermia group. The data were collected by taking rabbit liver biopsy samples and were analyzed in univariate and bivariate with Shapiro Wilk normality test, independent T-test and Mann Whitney. This study used 21 rabbits as sample, 3 were excluded and each group have 6 samples. Statistical analysis of the comparison of liver tissue damage scores between the control group and the ischemic precondition treatment group showed a significant difference with a p value 0.002 and the comparison of the liver tissue damage scores between the control group and the hypothermic treatment group showed significant differences with p value 0.004. It can be concluded that there are liver tissue damage as a result of ischemic reperfusion injury in experimental rabbits, and there are significant differences in liver tissue damage between the control group, the hypothermia and ischemic precondition group